Fiscal Transparency Handbook (2018). (Manuals and Guides, 2018)
The IMF's Fiscal Transparency Code is the international standard for disclosure of information about public finances and is the centerpiece of the global architecture on fiscal transparency. The Fiscal Transparency Handbook (2018) provides detailed guidance on the implementation of the new Fiscal Transparency Code, which was approved by the IMF Board in 2014. It explains why each principle of the Code is important and describes current trends in implementation of the principles, noting relevant international standards as well. Selected country examples are also provided.